Insomnia in chronic pain patients with and without major depressive disorder - Emery, Patricia C (University of Ottawa (Canada), 2006)
Insomnia and major depression are both common problems among people with chronic pain. Although each has been studied quite extensively in this population, they have seldom been considered together. Thus, the goal of the present research was to compare patients with chronic pain who either did or did not meet criteria for major depressive disorder, with a particular emphasis on measures of sleep and sleep disturbance. Thirty-three patients with chronic pain and comorbid major depression and 27 chronic pain patients without comorbid major depression completed structured diagnostic interviews on sleep and mood, and completed retrospective and 4-day diary measures of sleep, sleep-related behaviours, sleep-related cognitions, pain, and mood. The measures of sleep-related variables were selected because of their relevance to a cognitive-behavioural model of insomnia. A diagnosis of insomnia was highly prevalent in both groups, with fully 53 of 60 (88.3%) participants meeting DSM-IV criteria. Participants with major depression reported significantly higher levels of pain and more dysfunctional attitudes and behaviours related to sleep. They were also more likely to have sleep disorders other than insomnia. However, specific sleep parameters such as sleep onset latency, time awake after sleep onset, sleep efficiency, and total sleep time did not differ between the groups, whether they were assessed retrospectively or with daily diaries. Insomnia symptoms were highly associated with pain severity among participants with major depression; however, the majority of pain, sleep, and mood-related correlates of insomnia severity did not differ significantly between the groups. Partial correlation coefficients, controlling for pain severity, substantially decreased the associations between depression and cognitive-behavioural variables related to sleep, thus suggesting that pain may be more important than depression in the etiology of insomnia. That is, chronic pain itself may disturb sleep so extensively that comorbid depression has little incremental effect. The results are discussed in terms of the potential applicability of cognitive-behavioural interventions for insomnia in chronic pain patients with comorbid major depressive disorder.
Keywords: Psychology, Clinical.; Psychology, Physiological.